Perceived healthcare stigma among patients in opioid substitution treatment: a qualitative study - Lars Garpenhag; Disa Dahlman (BMC, 2021)
Abstract Background People with substance use disorders (SUD) including patients in opioid substitution treatment (OST) are subject to stigma, and have generally poor health and barriers towards seeking healthcare. Experience of stigma might negatively affect healthcare seeking, but this topic is sparsely investigated. The aim of this study was to explore OST patients' past and present experiences of substance use stigma in healthcare settings, in order to provide insight into the challenges that people with opioid use disorder may face when using health services, and the strategies they use to cope with them. Methods Six focus groups with 23 OST patients were moderated by OST staff, and conducted with a questioning route focusing on health literacy. Experiences associated with stigma and its consequences that were spontaneously brought up by participants were assessed in a secondary analysis using a thematic approach. Results Experiences of stigma from a wide range of healthcare settings were reported. Medical records and patients' oral information regarding substance use, OST medication or hepatitis C infection were identified as circumstances bringing unwanted attention to the SUD. Participants reported various forms of poor treatment, believed to reflect views of people with SUD as morally culpable, intimidating, curious, untrustworthy and less valuable than other patients, sometimes with tangible effects on the quality of healthcare. Stigma in healthcare settings affected healthcare seeking behaviors, and could result in patients concealing their OST status or substance use history. Conclusion This study highlights several aspects of perceived healthcare stigma that can shed light on difficulties that OST patients might experience when navigating the healthcare system. The results implicate a need to investigate attitudes towards OST patients, and the aptitude to deal with patients with SUD, among healthcare professionals, as well as a need for interventions addressing knowledge deficits and issues tied to values and patient reception among healthcare staff.